Optical and electronic properties of TiO2/GOQDs composites: A combined experimental and first-principles calculations study - Jauja-Ccana V.R. (2021)
In this work, the optical and electronic properties of a TiO2/graphene oxide quantum dots (GOQDs) composite were studied by experimental and computational methods. The experimental procedures were made on TiO2 and GOQDs nanoparticles synthesized by a sol-gel method and one-pot electrochemical carbonization, respectively. The characterization of these materials and the TiO2/GOQDs composite was made using field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), X-ray photoelectron microscopy (XPS), FT-IR spectroscopy, and dynamic light scattering (DLS). The experimental measurements of the optical properties of these materials by UV–Vis absorption spectroscopy indicate that the addition of GOQDs promotes the expansion of the radiation absorption of TiO2 towards the visible range. Similarly, photoelectrochemical tests performed to determine the electronic properties show that GOQDs improve the separation of the photogenerated electron-hole pairs, increasing the photocatalytic activity of the TiO2. These results were further contrasted with a computational study based on first-principles DFT-D3 calculations, using the projector augmented wave (PAW) method on TiO2, pristine GQDs, GOQDs, TiO2/GQDs, and TiO2/GOQDs clusters. The computational results showed that GOQDs exhibit properties of a p-type semiconductor due to the presence of oxygenated groups. Therefore, when used as TiO2/GOQDs composite, these form a type II heterojunction, increasing the photocatalytic activity of the material. © 2021 Elsevier B.V.